Pengawasan Dewan Perwakilan Rakyat Daerah dalam Pelaksanan APBD di Kota Malang (Studi di DPRD Kota Malang) - Franklin Asido Rossevelt (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Abstract: The Supervision of Regional Representatives Council Budgets Of Implementation In Malang. The background of this research is to ensure the efficiency of the delivery of the Government, and also to expanding as well as of the instrument in realizing democracy and public welfare. The Republic of Indonesia’s Law Number 32 Year 2004 on Local Government, and the Law of the Republic of Indonesia Number 33 Year 2004 on Financial Balance between Central and Regional Government wishes to put a political line Decentralized Autonomous Region by replacing the laws of the Republic of Indonesia Number 25 year 1999. Malang is one of the Regional Otononom Regional set by the central government. A significant problem in the Autonomous Region is a financial problem. To finance the necessities in one fiscal year Regional Revenue and Expenditure (budget) as the regional legislature has the right to supervise budget. Keyword: Regional Autonomy, The Supervision Budget, The efficiency of the delivery of the Goverment. Abstrak: Pengawasan Dewan Perwakilan Rakyat Dalam Pelaksanan APBD Di Kota Malang. Dengan latar belakang Otonomi Daerah diadakan untuk menjamin efisiensi penyelenggaran Pemerintah, juga untuk memperluas pelaksanaan demokrasi dan instrumen dalam mewujudkan kesejahteraan umum. Undang–Undang Republik Indonesia Nomor 32 Tahun 2004 tentang Pemerintahan Daerah, dan Undang–Undang Republik Indonesia Nomor 33 Tahun 2004 tentang Perimbangan Keuangan Antara Pemerintah Pusat dan Pemerintahan Daerah berkehendak meletakan suatu garis politik Otonomi Daerah menurut cara Desentralisasi menggantikan undang–undang Republik Indonesia Nomor 25 Tahun 1999. Kota Malang adalah salah satu Daerah Otonom yang ditetapkan oleh pemerintah pusat. Masalah yang cukup penting di Daerah Otonom adalah masalah keuangan. Untuk membiayai keperluan-keperluan Daerah dalam satu tahun anggaran Pendapatan dan Belanja Daerah (APBD) sebagai lembaga legislatif Daerah berhak untuk melakukan pengawasan terhadap pelaksanan APBD. Kata Kunci: Otonomi Daerah, Pengawasan APBD, Efisiensi Penyelenggaraan Pemerintahan